A self-binding immune complex vaccine elicits strong neutralizing responses against herpes simplex virus in mice - Diamos, Andrew G.; Pardhe, Mary D.; Bergeman, Melissa H.; Kamzina, Aigerim S.; DiPalma, Michelle P.; Aman, Sara; Chaves, Artemio; Lowe, Kenneth; Kilbourne, Jacquelyn; Hogue, Ian B.; Mason, Hugh S. (Frontiers in Immunology, 2023)
Introduction It has been known for over half a century that mixing an antigen with its cognate antibody in an immune complex (IC) can enhance antigen immunogenicity. However, many ICs produce inconsistent immune responses, and the use of ICs in the development new vaccines has been limited despite the otherwise widespread success of antibody-based therapeutics. To address this problem, we designed a self-binding recombinant immune complex (RIC) vaccine which mimics the larger ICs generated during natural infection. Materials and methods In this study, we created two novel vaccine candidates: 1) a traditional IC targeting herpes simplex virus 2 (HSV-2) by mixing glycoprotein D (gD) with a neutralizing antibody (gD-IC); and 2) an RIC consisting of gD fused to an immunoglobulin heavy chain and then tagged with its own binding site, allowing self-binding (gD-RIC). We characterized the complex size and immune receptor binding characteristics in vitro for each preparation. Then, the in vivo immunogenicity and virus neutralization of each vaccine were compared in mice. Results gD-RIC formed larger complexes which enhanced C1q receptor binding 25-fold compared to gD-IC. After immunization of mice, gD-RIC elicited up to 1,000-fold higher gD-specific antibody titers compared to traditional IC, reaching endpoint titers of 1:500,000 after two doses without adjuvant. The RIC construct also elicited stronger virus-specific neutralization against HSV-2, as well as stronger cross-neutralization against HSV-1, although the proportion of neutralizing antibodies to total antibodies was somewhat reduced in the RIC group. Discussion This work demonstrates that the RIC system overcomes many of the pitfalls of traditional IC, providing potent immune responses against HSV-2 gD. Based on these findings, further improvements to the RIC system are discussed. RIC have now been shown to be capable of inducing potent immune responses to a variety of viral antigens, underscoring their broad potential as a vaccine platform.